2010
DOI: 10.1177/1938965509356684
|View full text |Cite
|
Sign up to set email alerts
|

Current Research and Events in the Spa Industry

Abstract: From the start of the modern spa in the mid-twentieth century, the spa industry has grown substantially worldwide. Part of that growth involves spas of different types—each with its own business model, including day spas, hotel-based spas, resort spas, and destination spas. Regardless of the type of spa, most operations provide massage and nutrition-related services, with nutrition growing substantially in importance. Recession has trimmed the industry’s sails, but barriers to exit are substantial enough that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 1 publication
2
28
0
1
Order By: Relevance
“…Most of the customers were not willing to pay more and/or downgrade therapist and product quality for above-average ambience quality, which is consistent with the results of Kucukusta et al (2013). Price, however, is a common selection attribute in many industries including the spa industry (Tabacchi, 2010). In this study, the high price variable was not significant, which indicates that the customers were willing to pay more for better …”
Section: Results Of the Repeated Measures Logistic Regressionsupporting
confidence: 80%
See 2 more Smart Citations
“…Most of the customers were not willing to pay more and/or downgrade therapist and product quality for above-average ambience quality, which is consistent with the results of Kucukusta et al (2013). Price, however, is a common selection attribute in many industries including the spa industry (Tabacchi, 2010). In this study, the high price variable was not significant, which indicates that the customers were willing to pay more for better …”
Section: Results Of the Repeated Measures Logistic Regressionsupporting
confidence: 80%
“…For example, Kucukusta and Guillet (2014) investigated spa-goers at hotel spas in Hong Kong, and respondents from the Asia-Pacific region, Europe, and North America indicated that price was the most important attribute in the choice of a hotel spa in Hong Kong. This is likely because hotel day spa services in Hong Kong are expensive, and the spas in hotels are often more expensive than other types of spas (Tabacchi, 2010;Kucukusta et al, 2013).…”
Section: Nationalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The spa industry has grown internationally in all types of spas, including day spas, hotel-based spas, resort spas, and destination spas; however, the economy can impact the industry's growth and changes to spa offerings may need to be repackaged for continued success [20]. Snoj and Mumel [21] analyzed the service quality elements of health spas in Slovenia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hall (2013) points out that positive perspective of the future of Czech and Slovak spas are seen in the increasing number of families with children. Moreover, spa treatments and spa travelers see as one of the benefits of this type of tourism to enrich and develop better relationships not only with partners but also children (Tabacchi, 2010). For this reason, the paper deals with a research aimed at the current situation of spa services in the chosen Czech region aimed at target group family with children.…”
mentioning
confidence: 99%